Signaling pathways and axis formation in the lower metazoa - Holstein, Thomas W.; Watanabe, Hiroshi; Özbek, Suat (Growth factors in development, 2011)
The determination of the body axis in the last common ancestor of bilaterian animals is still a matter of debate. While Hox genes pattern the formation of the primary, anteroposterior body axis in bilaterians, there is growing evidence from lower metazoans that the Wnt/β-catenin pathway acts as the primordial signaling system in this process. This review summarizes molecular data from recent genomic analyses of basal model organisms with a focus on the evolution of signaling pathways involved in the establishment of the primary and successive body axes during early metazoan evolution.
Gesehen am 16.02.2017